Extraction-free RT-RPA assay for detection of HPV16, HPV18, and HPV45 mRNA expression - Emilie Newsham Novak; Ariel Ma; Kathryn A. Kundrod; Megan M. Chang; Cannon J. Hansen; Jane Richards Montealegre; Michael E. Scheurer; Philip E. Castle; Ming Guo; Mila P. Salcedo; Kathleen Schmeler; Rebecca Richards-Kortum (Scientific Reports)
Abstract Messenger RNA (mRNA) from high-risk genotypes of human papillomavirus (hrHPV) is a more specific biomarker for cervical cancer risk than hrHPV DNA due to its ability to differentiate clinically significant infections from transient ones. Detecting mRNA from exfoliated cervical cells, however, is a complex, expensive, and equipment-intensive process, making it infeasible in resource-limited settings. Here we describe a sensitive, specific, and minimally instrumented method to detect HPV16, HPV18, and HPV45 mRNA in exfoliated cervical cells. First, reverse transcription recombinase polymerase amplification (RT-RPA) exo assays were designed to amplify and detect HPV16, HPV18, and HPV45 E7 mRNA ≥100 copies per reaction in real time using a portable fluorimeter, which is on par with the only FDA-approved hrHPV mRNA test. Next, an extraction-free sample preparation method using only an enzymatic reaction was developed to lyse cells and degrade cellular DNA in cultured HPV16, HPV18, and HPV45-positive cells. The RT-RPA assays specifically amplified mRNA from this crude lysate across a clinically relevant range of concentrations. Eleven cervicovaginal samples were tested at the point of care using these methods and showed 100% agreement between RT-RPA and RT-qPCR results, including two samples that were positive for HPV16 mRNA. Additionally, nine negative samples spiked with HPV16, HPV18, and HPV45-positive cells successfully detected each respective HPV type. In total, this prototype assay has potential to make sensitive and specific hrHPV mRNA testing more accessible in resource-limited settings.